Outpatient pre-operative assessment in joint replacement surgery - Chan, C.Y.W.; Nam, H.Y.; Raveenthiran, R.; Choon, S.K.; Tai, C.C. (Malaysian Medical Association, 2008)
An anaesthetist-led outpatient pre-operative assessment (OPA) clinic was introduced in our unit in an effort to improve patient care and cost-effectiveness. To assess the efficiency of the clinic, 112 patients who attended the OPA clinic (attendance rate 98%) during the first year were assessed prospectively and compared with 118 patients who did not undergo OPA the year before. There were fewer cancellations among those who attended the OPA clinic (13.6% compared to 3.6%), and the hospital stay was shortened from an average of 10.7 days to 7.0 days. This has resulted in more efficient utilization of operating theatre, reduced hospital costs and improved patient satisfaction. More extensive use of the pre-admission clinic is recommended and should be explored in other clinical settings.